MODEL PEMBELAJARAN KONTEKSTUAL PADA MATA PELAJARAN PAI DI SMP AL-AZHAR BANJAR PATROMAN - M. Badrut Tamam (Institut Agama Islam Negeri Purwokerto, 2017)
This study describes the Contextual Teaching and Learning method for Islamic religion subject at SMP Al-Azhar Banjar Patroman. This research resulted in: 1) Islamic religion subject teachers perceived the students as subjects of teaching whose knowledge always developes in accordance with their experience; 2) The clasroom activities of Contextual Teaching and Learning method was implemented by creating a conducive learning atmosphere while for assessment was carried out thoroughly, on the cognitive, affective and psychomotor aspects; 3) The response of students to the Contextual Teaching and Learning method was good. It was shown from high learning motivation and anthusiastic involvement of the students in the learning, mostly the students reached above of KKM score and possessing good spiritual or social manners.